3D CFD simulations of trailing suction hopper dredger plume mixing: Comparison with field measurements - de Wit, Lynyrd; Talmon, A.M.; van Rhee, C. (Marine pollution bulletin, 2014)
A 3D computational fluid dynamics (CFD) model is used to simulate mixing of an overflow plume within 400 m from a trailing suction hopper dredger (TSHD). The simulations are compared with new field measurements. It is the first time simulations of overflow dredging plumes are compared in such detail to field measurements this close to a TSHD. Seven cases with a large variety in overflow flux and plume characteristics are used. Measured maximum suspended sediment concentrations (SSC) vary between 30 and 500 mg/l and fluxes vary between 0.7% and 20% of the total overflow flux; the CFD model has, subject to the limitations of the field data, been shown to reproduce this in a satisfactory way. The model gives better understanding of important near field processes, which helps to assess the frequency, duration and intensity of stresses like turbidity and sedimentation needed to find the environmental impact of dredging projects.